REFLECTIVE TEACHING DONE BY ENGLISH DEPARTMENT STUDENTS IN MICRO TEACHING CLASS - Susanti, Roza (Universitas Mahaputra Muhammad Yamin, 2023)
Reflective teaching is done to know the strength and weakness from process of teaching. Opening skill, arranging lesson skill, timing allocation skill, explaining skill, giving stimulus variation, and closing and evaluating skill were reflected by candidates of teacher in this research. This research used descriptive research in qualitative method. The purpose of this research was to know the implementation of reflective teaching in micro teaching class. The method of this research was descriptive research. The participants of this research were the sixth semester in micro teaching class at English department of STKIP Yayasan Abdi Pendidikan Payakumbuh. In collecting the data, the researcher applied observation, students’ journal, and recording. In analyzing data, the researcher used some steps, they are: data managing, reading/memoing, classifying, interpreting, and writing report. After doing the research, the researcher got the result that 63,3% students in micro teaching class were able to reflect themselves. Thus, the students were able to implement reflective teaching in micro teaching class.